Attitude of Consumers Towards Events Organized by Companies - Seturi, Maia; Surmava, Maka (Archives of Business Research, 2023)
After the transition to market relations, interest in various directions of marketing increased in Georgia. One of them is public relations, which helps companies to form and maintain a positive image. It, in turn, has various tools. Among them, the events are noteworthy. Planning them properly and implementation is important to ensure effective marketing management and achievement of set goals in the company. The purpose of the article is to study the attitudes of consumers towards the events carried out by Georgian companies. We used the form of an online survey, which is currently quite effective. Events play a major role in forming impressions of a company and its brands. Those companies that intelligently manage and implement events contribute to the formation of their positive image and increase in the promotion of their brands. Events are used by many subjects to impress other people. Business entities can gain goodwill from their target market by making a good impression on the public. With its correct planning and implementation, the company will receive economic benefits. In the article, the authors discuss the problems associated with conducting events, present the main results of the conducted research and recommendations in the direction of increasing the effectiveness of the use of events.